2014
DOI: 10.1002/jsfa.6986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cadmium and mycorrhizal fungi on the fatty acid profile of flax (Linum usitatissimum) seeds

Abstract: The pronounced effects of mycorrhizal fungi on the concentration of unsaturated fatty acids at 15 ppm Cd may have been due to the presence of elevated levels of Cd within seeds. Our results suggest that, once the concentration of cadmium within seeds reaches a certain threshold, this heavy metal may improve the efficiency of enzymes that convert saturated fatty acids to unsaturated fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…different plant species have been studied for phytoremediation of various metal contaminants [13,[28][29][30]. Among these plants, fibrous crops such as Linum usitatissimum [31], Hibiscus cannabinus [32] and Boehmeria nivea [15] have been used for phytoextraction of Cd, Cr and Cu. Jute (C. capsularis L.) is considered as potential candidate against stress condition than other fibrous crop, possibly owing to its specific biochemical and physiological responses [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…different plant species have been studied for phytoremediation of various metal contaminants [13,[28][29][30]. Among these plants, fibrous crops such as Linum usitatissimum [31], Hibiscus cannabinus [32] and Boehmeria nivea [15] have been used for phytoextraction of Cd, Cr and Cu. Jute (C. capsularis L.) is considered as potential candidate against stress condition than other fibrous crop, possibly owing to its specific biochemical and physiological responses [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Cid-Hernández's research also indicated that the activities of certain membrane bound enzymes can change with changes in membrane fluidity (Cid-Hernández et al, 2015). Additionally, Kaplan et al (2014) demonstrated that the positive effects of mycorrhizal fungi on the concentration of unsaturated fatty acids at 15 ppm Cd may have been due to an improvement in the efficiency of enzymes that convert saturated fatty acids to unsaturated fatty acids. To conclude, the SA-induced protection of membrane lipids, in 16-days-old flax plantlets treated during 10 days with toxic Cd concentrations, gave some enlightenment about to its potential function as Cd-stress elicitor and membrane stabilizer in roots.…”
Section: Discussionmentioning
confidence: 94%
“…Flax is a prominent source for linoleic (C18:2) and linolenic (C18:3) acids (Kaplan et al, 2014) and can survive on cadmium (Cd)-contaminated soils with minimal effects on above and belowground growth (Kaplan et al, 2014;Praczyk et al, 2015). Cd is a rare element, uniformly distributed in the earth's crust, where its average concentration is 0.15-0.20 mg kg À 1 (Fleischer et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid boosts root antioxidant mechanisms in flax. Kaplan et al [104] investigated the effects of cadmium stress on the fatty acid composition of flax in the presence of mycorrhizal fungi. They discovered that seeds from plants cultivated in mycorrhizal fungi contained more unsaturated (18:1, 18:2, and 18:3) fatty acids overall.…”
Section: Heavy Metal Stress Tolerancementioning
confidence: 99%